Dampak Implementasi Pertanian Berkelanjutan Terhadap Stabilitas Ekonomi Dan Pembangunan Daerah Tertinggal - Wulandari, Putu Riska (Jayapangus Press, 2025)
The real condition of the agricultural sector in underdeveloped areas, which still faces major challenges such as the need for agricultural products to be available in the long term and maintaining a balance between economic sustainability and environmental management. Sustainable agriculture is a commitment that must be implemented immediately, so that economic, ecological and social sustainability can be created. Several efforts have been made to support sustainable agriculture in underdeveloped areas which are expected to achieve more inclusive and sustainable economic development, namely the adoption of environmentally friendly agricultural practices, access to technology, and policies that support farmers in the transition to sustainable agriculture. This research aims to analyze the impact of implementing sustainable agricultural practices on economic stability and development in underdeveloped areas. This research uses a literature study method to analyze the impact of implementing sustainable agriculture on economic stability and development in underdeveloped areas. Sustainable agriculture has been proven to increase agricultural productivity, reduce dependence on synthetic chemicals, and preserve natural resources. Apart from that, this practice also has the potential to improve farmers' welfare by increasing income and strengthening food security. Therefore, to maximize the positive impact of sustainable agriculture, greater support is needed in the form of supportive policies, farmer empowerment, and financial incentives that can facilitate the transition to more environmentally friendly and inclusive agriculture.